Sui molteplici usi della pietà - Marassi, Massimo (Bollettino Filosofico, 2016)
In general, pity has always been conceived as a passion or as a virtue. These are two ways of looking at the concept, which are difficult to conciliate. Heidegger, in particular, considers pity as something which comes into play when the philosopher is asking questions about the beings and about the manifestation of the being. At the same time, he also considers pity as a form of passion. In this case, phenomenology abandons the primacy of intentionality and becomes an exaltation of the pathe. On the other hand, according to a different perspective, pity as a virtue embraces a wide range of experiences, from that of tragedy to solidarity. The latter two make it possible to have an ethics of existence. Pity works a priori, it precedes any question, it prefers justice over knowledge and it is a way of looking at things which needs no plea, no question to understand the necessity of existence.